Facile synthesis of hierarchical MoS2–carbon microspheres as a robust anode for lithium ion batteries. Issue 24 (7th June 2016) - Chen, Gen; Wang, Shengping; Yi, Ran; Tan, Longfei; Li, Hongbo; Zhou, Meng; Yan, Litao; Jiang, Yingbing; Tan, Shuai; Wang, Donghai; Deng, Shuguang; Meng, Xianwei; et al.
Abstract : MoS2 –C microspheres have been demonstrated with excellent electrochemical performances in terms of low resistance, high capacity even at large current density, and stable cycling performance. Abstract : Molybdenum disulfide (MoS2 ) may be a promising alternative for lithium ion batteries (LIBs) because it offers a unique layered crystal structure with a large and tunable distance between layers. This enables the anticipated excellent rate and cycling stability because they can promote the reversible lithium ion intercalation and de-intercalation without huge volume change which consequently prevents the pulverization of active materials during repeated charge and discharge processes. Herein, we prepared hierarchical MoS2 –carbon (MoS2 –C) microspheres via a continuous and scalable ultrasonic nebulization assisted route. The structure, composition, and electrochemical properties are investigated in detail. The MoS2 –C microspheres consist of few-layer MoS2 nanosheets bridged by carbon, which separates the exfoliated MoS2 layers and prevents their aggregation and restacking, thus leading to improved kinetic, enhanced conductivity and structural integrity. The novel architecture offers additional merits such as overall large size and high packing density, which promotes their practical applications. The MoS2 –C microspheres have been demonstrated with excellent electrochemical performances in terms of low resistance, high capacity even at large current density, stable cycling performance, etc. The electrodes exhibited 800 mA h g −1 at 1000 mA g −1 over 170 cycles. At a higher current density of 3200 mA g −1, a capacity of 730 mA h g −1 can be also maintained. The MoS2 –C microspheres are practically applicable not only because of the continuous and large scale synthesis via the current strategy, but also the possess a robust and integrated architecture which ensures the excellent electrochemical properties.